173k views
2 votes
Find the inverse function of f(x)= 1+squareroot of 1+2x

1 Answer

1 vote

Answer:

Therefore the inverse function of
f(x)=1+√(1+2x) is
(x^2-2x)/(2)

Step-by-step explanation:

We need to find the inverse of function
f(x)=1+√(1+2x)

Function Inverse definition :


\mathrm{If\:a\:function\:f\left(x\right)\:is\:mapping\:x\:to\:y,\:then\:the\:inverse\:functionof\:f\left(x\right)\:maps\:y\:back\:to\:x.}


y=1+√(1+2x)
\mathrm{Interchange\:the\:variables}\:x\:\mathrm{and}\:y


x=1+√(1+2y)


\mathrm{Solve}\:x=1+√(1+2y)\:\mathrm{for}\:y


\mathrm{Subtract\:}1\mathrm{\:from\:both\:sides}


1+√(1+2y)-1=x-1

Simplify


√(1+2y)=x-1


\mathrm{Square\:both\:sides}


\left(√(1+2y)\right)^2=\left(x-1\right)^2


\mathrm{Expand\:}\left(√(1+2y)\right)^2:\quad 1+2y


\mathrm{Expand\:}\left(x-1\right)^2:\quad x^2-2x+1


1+2y=x^2-2x+1


\mathrm{Subtract\:}1\mathrm{\:from\:both\:sides}


1+2y-1=x^2-2x+1-1


\mathrm{Simplify}


2y=x^2-2x


\mathrm{Divide\:both\:sides\:by\:}2


(2y)/(2)=(x^2)/(2)-(2x)/(2)


\mathrm{Simplify}


y=(x^2-2x)/(2)

Therefore the inverse function of
f(x)=1+√(1+2x) is
(x^2-2x)/(2)

User Netlander
by
5.4k points